(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the present research work was to develop the biodegradable polymeric implant for the delivery of antineoplasticdrug, paclitaxel (PTX) using poly (sebacicâ€coâ€recinoleic acid) 70:30 w/w. PTX loaded implants were prepared by indigenously developed melt molding technique. Implants were characterized in terms of physicoâ€chemical evaluations, drug content, drug stability and intactness, thermal analysis, drug physical state and crystallinity, surface morphology, hydrolytic degradation, drug release and its kinetics. Prepared implants were yellow and cylindrical in shape with smooth surfaces.Drug in the implants was found to be stable, intact and uniformly dispersed as amorphous state within the polymer matrix. In vitro release, kinetic studies showed zero order and Korsmeyerâ€Peppas model release being exhibited. Drug release from the polymeric implants was occurred could be as results of diffusion.